Biometric and morphological adjustments of Eugenia. dysenterica DC. seedlings in response to increased soil water deficit - Matheus Pena Campos; José Carlos Moraes Rufini; Bruno Montoani Silva; Mayara Neves Santos Guedes; Yesenia Mendoza García; Janaina Canaan Rezende de Souza; Raphael Passaglia Azevedo; Miriã Cristina Pereira Fagundes (Acta Scientiarum. Biological Sciences, 2023)
Water stress can affect all aspects of plant growth and development, compromising its productive potential. The cultivation of fruit species native to the Cerrado and the study of their behavior under conditions of low water availability are necessary activities, in view of their socioeconomic and environmental potential. This study was conducted to evaluate the effect of water deficit on growth and biomass production of the cagaita tree (Eugenia dysenterica DC.), a species endemic to the Cerrado (Brazilian Savannah). The experiment was performed in a greenhouse for 120 days in a randomized block design (RBD), with a double factorial arrangement (2x5), corresponding to two cagaita mother plants and five water conditions. We evaluated the growth and leaf, stem and root functional characteristics. The most severe water deficit conditions reduced shoot growth, number of leaves, production of biomass and dry matter and increased the specific and per plant mass root length of cagaita plants. Deficit extension had negative effects on its growth and development. There was a statistical difference between mother plants, with mother plant 2 being more resistant to drought. The application of a severe or longer water deficit affected shoot growth and reduced the appearance of new leaves. The stress caused by water deficiency allowed an increase in root functional characteristics, supporting the hypothesis that plants under adverse conditions focus on higher biomass production and convert a higher amount of dry matter into the roots. Leaf area did not show to be a functional characteristic, explaining the stress effects in E. dysenterica DC plants.